Heterosis and character association of mid altitude adapted quality protein maize (Zea mays L.) hybrids at Bako, Western Ethiopia - Beyene Abebe; Wassu Mohammed Ali; Adefris Teklewold Chere (Open Journal of Plant Science - Peertechz Publications, 2020)
The production of hybrid Quality Protein Maize (QPM) is started very recently in Ethiopia that requires extensive research to exploit heterosis to increase the productivity of the crop. Exploitation of heterosis through the production of hybrids is proven breeding method to improve the yield of maize. Accordingly, the aims of this study were to estimate the magnitude of heterosis of QPM inbred lines and to determine the association among morph-agronomic traits. The crossing and experiment were conducted at Bako National Maize Research Center during the 2014 and 2015 main cropping season, respectively. Forty-five F1 hybrids obtained by crossing 10 inbred lines in diallel fashion were planted in two separate trials on adjacent experimental blocks. The experimental design used was alpha lattice for the hybrid trial and randomized complete block design for inbred lines trial with three replications. Each entry was planted on a one-row plot of 5.1 m length with 0.75 m and 0.3 m spacing between rows and plants, respectively for both trials. Data on phenology, growth, grain yield and yield related traits, and disease reaction were collected at the appropriate plant growth stages. The mean squares due to hybrids and parents were highly significant for all traits except common leaf rust in the hybrids trial and diseases parameters, stem lodging, bad husk cover and ear rot indicating the existence of genetic variability for most traits. The highest positive mid and better parents heterosis was observed for grain yield and yield related traits indicating the possibility of increasing grain yield and yield related characters via hybridization. Negative heterosis was observed for phenology and growth traits and diseases parameters as well. Grain yield had highly significant positive association with plant height, ear plant-1, ear length and number of kernel row-1and negatively correlated with anthesis silk interval, plant and ear aspect, common lea rust, phaeosphaeria leaf spot and ear rot at genotypic and phenotypic level. In addition, plant height, ear plant-1, ear length, number of kernel row- had positive direct effects and anthesis silk interval, plant aspect, phaeosphaeria leaf spot and ear rot had negative direct effects on grain yield at both genotypic and phenotypic level; while, common leaf rust had negative direct effects at genotypic and days to anthesis, ear height, root lodging and ear aspect had negative direct effects on grain yield at phenotypic level. This indicated that, by increasing the positive and decreasing the negative direct effects of the traits grain yield could increase invariably.